Digitalization and Business Transformation: Young MSME Practitioners' Perspectives on Current Economic Changes - Sjahruddin, Herman; Chatra, Afdhal; Ernawati, Ernawati; Saefudin, Arif; Launtu, Ansir (Journal The Winners, 2024)
The COVID-19 pandemic has forced many businesses to shut down their operations and shift to digital platforms to survive and ensure their business continues. Hence, Micro, Small, and Medium Enterprises (MSMEs) have undergone an accelerated digital transformation to adopt technological innovations. The research aimed to identify the factors that encouraged and hindered digital innovation in MSMEs during economic destabilization, focusing on the perspectives of young entrepreneurs in Makassar City. Qualitative methods were used, involving in-depth interviews with 25 young entrepreneurs in Makassar City to explore the positive and negative impacts of transitioning to digital platforms post-pandemic. Data analysis was conducted using the inductive content analysis method. The results show that digital innovation in MSMEs after the pandemic is influenced by external factors (market and demand restrictions) and internal factors (personal and professional development). The limited financing, technology, and management of MSMEs compared to large enterprises make them more vulnerable to post-pandemic bankruptcy. Barriers faced in running businesses post-pandemic include market challenges on digital platforms, the need for necessary skills, and infrastructure availability. The implications of these findings are expected to develop programs that support young entrepreneurs and provide recommendations for the government in formulating policies and strategies to encourage digital entrepreneurship, especially in developing countries after the current pandemic.